Adsorption of copper ions onto chitosan/poly(vinyl alcohol) beads functionalized with poly(ethylene glycol). (15th April 2020) - Trikkaliotis, Dimitrios G.; Christoforidis, Achilleas K.; Mitropoulos, Athanasios C.; Kyzas, George Z.
Graphical abstract: Highlights: A novel adsorbent material composed of chitosan polyvinyl alcohol and polyethylene glycol was prepared. Efficient removal of copper ions from aqueous solutions. Characterizations with SEM, XRD, EDS, AFM and FTIR. The maximum adsorption was observed equal to 99.99 %. Abstract: A novel adsorbent material composed of chitosan (Cs), polyvinyl alcohol (PVA) and polyethylene glycol (PEG) was prepared in hydrogel bead form to efficiently remove copper ions from aqueous solutions. The properties of the composite were characterized by scanning electronic microscopy (SEM), X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDS), atomic force microscopy (AFM) and Fourier transform infrared spectroscopy (FTIR). The adsorption behavior of Cu(II) onto Cs/PVA/PEG beads was studied as a function of solution pH, temperature and contact time. The maximum adsorption was observed equal to 99.99 % for initial copper ion concentration of 25 mg/L at pH 5, temperature 45 °C, 5 h as contact time and 1 g/L of adsorbent dose. Langmuir isotherm and pseudo-second kinetic model fitted the experimental data sufficiently. Thermodynamic studies indicated that the process was spontaneous and endothermic. Cs/PVA/PEG beads can act as an effective adsorbent for the removal of Cu(II) from aqueous solution.